Penggunaan Metode Analisis Tugas dalam Meningkatkan Kemampuan Bina Diri Berpakaian Seragam pada Anak Tunagrahita Sedang di SLB Negeri Halmahera Barat - Abdullah Hi Ishak (Jurnal Ilmiah Wahana Pendidikan, 2020)
The purpose of this study was to get a clear picture of the use of task analysis methods in overcoming the problem of children's inability to wear uniforms. The study was conducted at SLB Negeri Halmahera Barat, where a retarded child was found who could not wear his own clothes and still needed someone else. Task analysis method is a method of sequential small steps that are used to help solve a problem and can minimize the problem that is done repeatedly. This study used an experimental study in the form of a Single Subject Research (SSR), with the research design A - B - A. The research subjects were mentally retarded children who could not wear uniforms. The results showed how the use of analytical methods can improve the ability of self-development to wear uniforms in retarded children in class I in SLB Negeri Halmahera Barat